Awareness and Perceptions of Exclusive Breastfeeding as a Method of Birth Control Among Catholic Pregnant Women Attending Antenatal Clinics in Rural Communities - Isaac John Umaru; Hauwa A. Umaru; Tyem Lawal Danjuma; Solomon O. Asare; Inemesit Samuel Essien; Ingwu Joseph Akem; Genevieve A. Yeboah; Julius Ishaya Salman; Katchin Evelyn Shadrach; Maryam Usman Ahmed (Darul Yasin Al Sys, 2026)
Although exclusive breastfeeding (EBF) is widely recognized for its nutritional and immunological benefits, its role as a natural contraceptive through the Lactational Amenorrhea Method (LAM) remains insufficiently understood, particularly in rural communities where cultural and religious beliefs shape reproductive decisions. This study aimed to assess the level of awareness, perceptions, and barriers to the adoption of EBF as a method of birth control among Catholic pregnant women attending antenatal clinics in rural communities, while also examining the influence of education and religious beliefs on knowledge and acceptance of LAM. A quantitative survey design was employed using a structured questionnaire administered to 165 Catholic pregnant women. The instrument covered demographic characteristics, awareness of EBF and LAM, perceptions and beliefs, and barriers to adoption. Data were analyzed using descriptive statistics and chi-square tests to examine associations between variables. The findings showed that most respondents were aged 25–34 years (47.3%) and married (84.8%). Although 61.8% had heard of EBF as a birth control method, only 35.2% were familiar with the term LAM, and only 25.5% understood its three effectiveness criteria. Perceptions were mixed, with 47.9% considering EBF a reliable method and 59.4% believing that it aligns with Catholic teachings. The main barriers identified were lack of counseling (51.5%), cultural pressure (43.6%), and fear of pregnancy despite amenorrhea (36.4%). Education level was significantly associated with awareness of LAM (p = 0.03). The study concludes that, despite the perceived compatibility of natural family planning with Catholic teaching, substantial informational and practical barriers continue to limit informed adoption of EBF as a contraceptive method in rural settings. These findings contribute to a better understanding of the gap between religious acceptance and practical knowledge, and underscore the need for strengthened health education, engagement of religious leaders, and literacy-sensitive interventions to support safe and informed use of EBF for birth control.